330,000 farmers in Honduras and Colombia use tailored seasonal forecasts - CGIAR Research Program on Climate Change, Agriculture and Food Security; International Center for Tropical Agriculture (2016)
Providing climate information services to the most vulnerable communities remains a challenge. To overcome this challenge, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) together with the International Center for Tropical Agriculture (CIAT), set up Local Technical Agroclimatic Committees (LTACs) in Colombia and Honduras. These committees work closely together with government institutions, civil society, meteorological-services and farmers to formulate specific agroclimatic recommendations. The LTACs also decide which climate-smart practices are to be implemented based on the climate information provided by CIAT and CCAFS.